2023
DOI: 10.1007/s13311-022-01287-8
|View full text |Cite
|
Sign up to set email alerts
|

A Mouse Model of Multiple System Atrophy: Bench to Bedside

Abstract: Multiple system atrophy (MSA) is a rare neurodegenerative disorder with unclear etiology, currently difficult and delayed diagnosis, and rapid progression, leading to disability and lethality within 6 to 9 years after symptom onset. The neuropathology of MSA classifies the disease in the group of a-synucleinopathies together with Parkinson’s disease and other Lewy body disorders, but features specific oligodendroglial inclusions, which are pathognomonic for MSA. MSA has no efficient therapy to date. Developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 113 publications
0
2
0
Order By: Relevance
“…Using ultracentrifugation on brain homogenates, the authors showed that only fractions enriched in Sarkosyl-insoluble αSyn aggregates were seedingcompetent, with MSA fractions being 100 times more potent than PD homogenates to induce aggregation in a cell model. It should be noted, though, that in these studies, MSArelated αSyn fibrils injection did not faithfully recapitulate the MSA pathology, affecting primarily neurons [48]. This is not true for non-human primates, where injections of GCI induce an MSA-like pathology with loss of oligodendrocytes and gliosis [49].…”
Section: Pd Msa and Dlb-derived Fibrils Induce Different Pathologiesmentioning
confidence: 66%
“…Using ultracentrifugation on brain homogenates, the authors showed that only fractions enriched in Sarkosyl-insoluble αSyn aggregates were seedingcompetent, with MSA fractions being 100 times more potent than PD homogenates to induce aggregation in a cell model. It should be noted, though, that in these studies, MSArelated αSyn fibrils injection did not faithfully recapitulate the MSA pathology, affecting primarily neurons [48]. This is not true for non-human primates, where injections of GCI induce an MSA-like pathology with loss of oligodendrocytes and gliosis [49].…”
Section: Pd Msa and Dlb-derived Fibrils Induce Different Pathologiesmentioning
confidence: 66%
“…Extensive animal studies are beginning to clarify the contribution of various forms of alpha-synuclein to the pathology (Peelaerts and Baekelandt [5]), to elucidate the mechanisms of disease spread first suspected on the basis of human postmortem pathological studies (Pinto-Costa et al [6]), and to model previously neglected non-motor aspects of Parkinson's disease (as reviewed by Richter et al [7]). Furthermore, Stefanova [8] shows how genetic manipulations in mice led to the generation of a model of Multiple Systems Atrophy, a rare disease in which alphasynuclein surprisingly accumulates in glial cells rather than in neurons. Each of these models contributes to a better understanding of synucleopathies, and some provide meaningful tools for the preclinical testing of novel therapies [7,8].…”
mentioning
confidence: 99%
“…Furthermore, Stefanova [8] shows how genetic manipulations in mice led to the generation of a model of Multiple Systems Atrophy, a rare disease in which alphasynuclein surprisingly accumulates in glial cells rather than in neurons. Each of these models contributes to a better understanding of synucleopathies, and some provide meaningful tools for the preclinical testing of novel therapies [7,8]. In the absence of a neuroprotective treatment that has been validated in the clinic, their predictability remains uncertain.…”
mentioning
confidence: 99%